A Glycine soja methionine sulfoxide reductase B5a interacts with the Ca2+/CAM‐binding kinase GsCBRLK and activates ROS signaling under carbonate alkaline stress. (7th July 2016) - Sun, Xiaoli; Sun, Mingzhe; Jia, Bowei; Qin, Zhiwei; Yang, Kejun; Chen, Chao; Yu, Qingyue; Zhu, Yanming
Summary: Although research has extensively illustrated the molecular basis of plant responses to salt and high‐pH stresses, knowledge on carbonate alkaline stress is poor and the specific responsive mechanism remains elusive. We have previously characterized a Glycine soja Ca 2+ /CAM‐dependent kinase GsCBRLK that could increase salt tolerance. Here, we characterize a methionine sulfoxide reductase (MSR) B protein GsMSRB5a as a GsCBRLK interactor by using Y2H and BiFc assays. Further analyses showed that the N‐terminal variable domain of GsCBRLK contributed to the GsMSRB5a interaction. Y2H assays also revealed the interaction specificity of GsCBRLK with the wild soybean MSRB subfamily proteins, and determined that the BoxI/BoxII‐containing regions within GsMSRBs were responsible for their interaction. Furthermore, we also illustrated that the N‐terminal basic regions in GsMSRBs functioned as transit peptides, which targeted themselves into chloroplasts and thereby prevented their interaction with GsCBRLK. Nevertheless, deletion of these regions allowed them to localize on the plasma membrane (PM) and interact with GsCBRLK. In addition, we also showed that GsMSRB5a and GsCBRLK displayed overlapping tissue expression specificity and coincident expression patterns under carbonate alkaline stress. Phenotypic experiments demonstrated that GsMSRB5a and GsCBRLK overexpression in Arabidopsis enhanced carbonate alkaline stress tolerance. Further investigations elucidated that GsMSRB5a and GsCBRLK inhibited reactive oxygen species (ROS) accumulation by modifying the expression of ROS signaling, biosynthesis and scavenging genes. Summarily, our results demonstrated that GsCBRLK and GsMSRB5a interacted with each other, and activated ROS signaling under carbonate alkaline stress. Significance Statement: Carbonate alkaline stress is a widespread environmental problem that severely restricts crop production. The basic mechanisms used by plants to respond to this stress are less characterized than responses to salt and high‐pH stresses. Here we use a wild soybean species that is tolerant to carbonate alkaline stress to describe a methionine sulfoxide reductase that interacts with a previously described protein kinase implicated in stress tolerance, to affect ROS signaling.